Konsep Rahn sebagai Instrumen Pembiayaan Syariah Analisis Rukun, Syarat dan Praktik Inovatif dalam Lembaga Keuangan Syariah - Novayanti, Sonia Fitri; Ramandhani, Reka Septianik Fajar; Rahmadani, Chusnul; Belvania, Nadhira Farras; Maharani, Dewi; Kurniawan, Taufiq (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The concept of Rahn as a sharia financing instrument offers financing solutions that are in line with sharia principles, especially to avoid riba (interest), gharar (uncertainty), and maysir (gambling). Rahn, which is a pawn agreement, can guarantee financing by using assets as collateral. This mechanism also provides certainty for lenders while facilitating access to funds for borrowers. This study examines the basic pillars and conditions that make a Rahn contract valid and identifies innovative practices applied by Islamic financial institutions in Indonesia. Using a literature review and descriptive analysis of applicable regulations and institutional practices, this research is useful for explaining how Rahn can help mitigate financing risks and promote financial inclusion. Despite its advantages, there will be challenges such as a lack of understanding among customers and issues related to collateral suitability, which remain significant. Therefore, ongoing customer education about the benefits and procedures of Rahn, as well as product innovation that is adaptive to market needs, is very important to optimize the function of Rahn in the framework of sharia financing. The research findings indicate that, first, the implementation of Rahn contracts provides benefits for Islamic banks in reducing the risk of non-performing loans, while also making it easier for customers to obtain financing with clear collateral. Finally, the research findings show that Rahn not only secures the financing process but also supports the growth of ethical and inclusive financial services in the Islamic finance sector. In conclusion, this study recommends improving customer education and strengthening regulations that support the implementation of rahn contracts in Islamic banking, and shows that customer education and continuous product innovation are very important for rahn to function optimally in Islamic financing.